Debt Accounting System Analysis in Accounting Information Systems - Humaira, Rauzhatul; Hazmi, Yusri; Nabila, Jihan; Ardiansyah, Fajar (West Science Interdisciplinary Studies, 2024)
The Debt Information System and Accounting Information System support and collaborate with each other to ensure that the company's financial information is well managed, regulatory compliance is maintained, and the right business decisions can be taken. This research uses a literature study method with the data used is secondary data. The research results show that the Debt Accounting System and the Accounting Information System are interrelated in processing and producing financial reports, especially in this case company debt. This is also supported by the sophistication of information technology, user capabilities, user participation, and top management support.